How the interplay of imagined contact and first‐person narratives improves attitudes toward stigmatized immigrants: A conditional process model. (26th June 2018) - Igartua, Juan‐José; Wojcieszak, Magdalena; Kim, Nuri
Abstract: This article assesses the mechanisms whereby first‐person narratives featuring stigmatized immigrants improve outgroup attitudes and encourage intergroup contact among prejudiced individuals. We rely on a 2 (imagined contact vs. control) × 2 (similar vs. dissimilar message protagonist) experiment on a systematic sample of native British adults. Results show that encouraging imagined contact prior to reading a short testimonial featuring an immigrant protagonist who is similar to the recipients in terms of social identity enhances identification with the protagonist, thereby improving outgroup attitudes and encouraging intergroup contact, and especially strongly among those who are prejudiced toward immigrants (i.e., high on modern racism). Theoretical and practical implications of the findings for the work on imagined contact, narrative persuasion, and identification, as well as for public communication campaigns, are discussed.